2016
DOI: 10.1177/0734282916668996
|View full text |Cite
|
Sign up to set email alerts
|

Do Cognitive Patterns of Strengths and Weaknesses Differentially Predict Errors on Reading, Writing, and Spelling?

Abstract: This study investigated the relationship between specific cognitive patterns of strengths and weaknesses (PSWs) and the errors children make in reading, writing, and spelling tests from the Kaufman Test of Educational Achievement-Third Edition (KTEA-3).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 52 publications
0
7
1
Order By: Relevance
“…As a result, students with similar broad ability profiles may have differed in their profile of narrow abilities, which could have increased heterogeneity within groups. In contrast to the findings of the present study, Liu et al (2017) found that particular profiles of strengths and weaknesses differentially predict error performance across several tests of reading and writing, and Koriakin et al (2017) found that particular profiles of strengths and weaknesses differentially predict error performance across tests of mathematics. The results of the present study along with the Liu et al and Koriakin et al studies suggest that the measures used to determine profiles may be an important sampling consideration for identifying group differences.…”
Section: Limitations and Future Directionscontrasting
confidence: 99%
See 1 more Smart Citation
“…As a result, students with similar broad ability profiles may have differed in their profile of narrow abilities, which could have increased heterogeneity within groups. In contrast to the findings of the present study, Liu et al (2017) found that particular profiles of strengths and weaknesses differentially predict error performance across several tests of reading and writing, and Koriakin et al (2017) found that particular profiles of strengths and weaknesses differentially predict error performance across tests of mathematics. The results of the present study along with the Liu et al and Koriakin et al studies suggest that the measures used to determine profiles may be an important sampling consideration for identifying group differences.…”
Section: Limitations and Future Directionscontrasting
confidence: 99%
“…Due to sample size limitations, distinct phonological and orthographic groups were not feasible. However, the error factor scores of students with phonological processing weaknesses may differ from those of students with orthographic processing weaknesses, as shown in Liu et al (2017). Combining these profiles into one group may have obscured group differences in error factor scores.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
“…In a rapid letter naming task, respondents read letters aloud and the time spent naming the letters is recorded. For example, Liu et al (2017) used the Letter Naming Facility task from the Kaufman Test of Education Achievement (Kaufman & Kaufman, 2014) to measure orthographic processing.…”
Section: Existing Assessments Of Orthographic Processingmentioning
confidence: 99%
“…Liu and colleagues (2017) also found that Gc was an important broad ability for basic reading skills, reading comprehension, and written expression. In almost every case, the high Gc group outperformed all other groups in the study on the phonological processing, word reading, and decoding error factors.…”
Section: Performance On Cognitive and Linguistic Processes Also Informentioning
confidence: 90%